Choosing optimal separator design using hierarchy analysis - D. A. Ozherelev; V. V. Shalay (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article describes the possibility of using the «Method of analysis of hierarchies» when choosing the type of separator. These calculation methods are used to determine the vector of priorities and alternatives according to specified criteria, as well as to assess the consistency of expert opinions. The task is set, alternative options and criteria for selecting a separator design are presented. A hierarchical structure is built for various designs of separators. The method of calculation for a variety of indicators that characterize the types of separation equipment is presented. Based on the results presented in accordance with the technical and economic indicators, the optimal design of the separator is determined